Amplification and Adaptation in the Ethylene Signaling Pathway. Issue 8 (1st October 2019) - Azhar, Beenish J.; Zulfiqar, Alveena; Shakeel, Samina N.; Schaller, G. Eric
Abstract: Plants are exquisitely sensitive to the ethylene signal and also respond to a much wider range of ethylene concentrations than would seem possible based on the simple circuitry of its primary signal transduction pathway, suggesting the existence of mechanisms for amplification and adaptation to ethylene signals. Here, such regulatory systems are considered within the context of what is known about the plant ethylene signaling pathway as well as signaling by the animal G‐protein coupled receptors, and the bacterial methyl‐accepting chemotaxis proteins. Magnitude amplification and sensitivity amplification mechanisms are considered as strategies for amplification of the ethylene signal. Several families of negative feedback regulators that desensitize plants to ethylene and thereby facilitate the ethylene adaptation response of plants are described. These negative feedback regulators include the ethylene receptors themselves, the RTE1/GR family, and the ARGOS family, all of which function at the level of the ethylene receptors to desensitize plants to ethylene. These negative regulators also include the EBF family of F‐box proteins, which target the EIN3/EIL family of transcription factors for degradation. Ethylene signal amplification and adaptation employ both transcriptional and post‐transcriptional regulation. Abstract : This review summarizes mechanisms for amplification and adaptation that allow plants to be exquisitely sensitive to the ethylene signal and also respond to a much wider range of ethylene concentrations than would seem possible based on the simple circuitry of the ethylene primary signal transduction pathway.